Control of foot-and-mouth disease in a closed society: A case study of Soviet Estonia - Kass, Marko; Viltrop, Arvo; Prakofjewa, Julia; Sõukand, Renata; Kalle, Raivo (Frontiers in Veterinary Science, 2022)
Foot-and-mouth disease (FMD) is a dangerous infectious disease of even-toed ungulate, however since 1991, the European Union has banned preventive vaccination. During the occupation of the USSR, there were two outbreak in Estonia: first started in 1952 (at that time the barns where about twenty animals); and second began in 1982 (a period of large barns period where several hundred animals). Neither outbreak was reported to the international community. At that time it was also forbidden to talk about the disease in the internal media, and speakers could be punished. Our study sought to find answers to how the disease was treated and repelled in the Estonian SSR on how infected animals and milk were handled and if some methods can be applied today. We used written and archival sources and 29 interviews with specialists remembering the outbreaks. Preventive slaughter of animals in the USSR was prohibited during the outbreak. As a preventive measure was used vaccination, people were restricted travelling out of the counties and disinfection mats were used on the roads. In already sick animals, udder wounds were treated with various wound ointments, like zinc ointment, but also ointment what is made of boiled spruce resin. Birch tar was also recommended in the literature for leg treatments. Mouth wounds were washed with potassium permanganate water. Workers used rubber gloves when handling sick animals. The barns were disinfected with lime and ash water. The milk of the diseased cows was pasteurize with local heaters and given to calves, pigs or diseased animals. Animals that did not recover were transferred to a meat processing plant. The meat was kept in potassium permanganate water before processing and canned or made into sausages. When the disease was discovered, the workers were locked in barns and released only when the disease was gone. Such an inhumane method could only be practiced in a totalitarian society, however, the potential disease control options speak in the favour of small farms where it is easier to treat small number of animals.